Oral cancer imaging: the principles of interpretation on dental radiograph, CT, CBCT, MRI, and USG - Rini Widyaningrum; Arif Faisal; M. Mitrayana; Munakhir Mudjosemedi; Dewi - Agustina (Majalah Kedokteran Gigi Indonesia, 2018)
Oral cancer is a malignant neoplasia on the lip and oral cavity. It is generally late-detected, locally invasive, and it has a high propensity for cervical lymph node metastases as well as blood-borne distant metastases. Diagnostic imaging for oral cancer is generally performed using conventional radiography, Cone Beam Computed Tomography (CBCT), Computed Tomography (CT), ultrasonography (USG), Magnetic Resonance Imaging (MRI), Positron Emission Tomography (PET), Single-Photon Emission Computed Tomography (SPECT), and bone scintigraphy. This review provides a general overview of oral cancer imaging and basic principles of interpretation for oral cancer using several imaging modalities. The selection of imaging modalities for oral cancer must be based upon clinical condition, availability of imaging modalities, and cost effectivity. Despite the limited availability of modern imaging modalities in Indonesia, understanding on the major concept of various oral cancer imaging and its interpretation are certainly required by the dentists. Imaging and its interpretation are required to assist the diagnosis and determine the most appropriate treatment plan. Thus, the survival rate can be improved.